The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.26508/lsa.202201880
|View full text |Cite
|
Sign up to set email alerts
|

ACE2-EGFR-MAPK signaling contributes to SARS-CoV-2 infection

Abstract: SARS-CoV-2 triggered the most severe pandemic of recent times. To enter into a host cell, SARS-CoV-2 binds to the angiotensin-converting enzyme 2 (ACE2). However, subsequent studies indicated that other cell membrane receptors may act as virus-binding partners. Among these receptors, the epidermal growth factor receptor (EGFR) was hypothesized not only as a spike protein binder, but also to be activated in response to SARS-CoV-2. In our study, we aim at dissecting EGFR activation and its major downstream signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…18 In addition, advanced docking analysis between EGFR and SARS-CoV-2 S protein in glioma cells showed a similar binding affinity to that between ACE2 and S protein. 52,59 These findings highlight a significant correlation between EGFR activation and regulation of SARS-CoV-2 infection.…”
Section: Activation Of Epidermal Growth Factor Receptor Signalling In...mentioning
confidence: 77%
See 1 more Smart Citation
“…18 In addition, advanced docking analysis between EGFR and SARS-CoV-2 S protein in glioma cells showed a similar binding affinity to that between ACE2 and S protein. 52,59 These findings highlight a significant correlation between EGFR activation and regulation of SARS-CoV-2 infection.…”
Section: Activation Of Epidermal Growth Factor Receptor Signalling In...mentioning
confidence: 77%
“…20 Meanwhile, S protein of SARS-CoV-2 activates MAPK through the ACE2-EGFR axis, which may facilitate the SARS-CoV-2 infection. 52 These studies suggest that the S protein of SARS-CoV-2 interacts with EGFR and this interaction may be involved in SARS-CoV-2 replication. The EGFR gene expression is also promoted at transcriptional levels upon SARS-CoV-2 infection, as it elevates mitochondrial bioenergetics and promotes the process of oxidative phosphorylation (OXPHOS) to induce robust virus propagation.…”
Section: Activation Of Epidermal Growth Factor Receptor Signalling In...mentioning
confidence: 88%
“…4 ). Considering the top ten enriched pathways, the phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/Akt) signaling and the EGFR tyrosine kinase inhibitor resistance, two pathways associated to SARS-CoV-2 infection 31 , 32 , were predominantly enriched in both Severe and Moderate cases. In contrast, miRNA targets enriched in the age-associated receptor for advanced glycation endproducts (AGE-RAGE) signaling, a pathway associated to COVID-19 severity 33 , were only observed in patients requiring intensive care (severe cases).…”
Section: Resultsmentioning
confidence: 99%
“…Pre-infection positive regulation of MAPK-ERK1/2 pathways showed a positive correlation with AT2s’ susceptibility to SARS-CoV-2 infection and postinfection viral load. A recent study showed that treatment of Caco-2 cells with SARS-CoV-2 spike protein’s receptor binding domain activated the key mediators (ERK1/2 and CRAF) of MAPK signaling, and inhibition of MAPK signaling by MEK inhibitors reduced SARS-CoV-2 infection [ 66 ].…”
Section: Discussionmentioning
confidence: 99%